Upaya peningkatan mutu pendidikan sekolah menengah kejuruan melalui pengembangan profesionalisme guru - Cok Istri Raka Marsiti (Jurnal Pendidikan Vokasi, 2011)
THE EFFORTS TO IMPROVE THE QUALITY OF VOCATIONAL HIGH SCHOOL EDUCATION THROUGH THE DEVELOPMENT OF TEACHER PROFESSIONALISMEducation is a key in improving quality of the nation. Human resource development is a strategic attempt that should be carried out by the government. Professional teacher is a whole building that covers thinking and acting in learning activities. As a consequence evaluation instrument of competency is a building unit that can be used to measure teachers competency. Professional teacher requires professional in teaching and training. Teachers roles are to generate learning activity, however, they face problems in executing their tasks, community perceptions on teachers, and teachers prosperity. Therefore, regeneration of teachers and continued development of human resource are answering these problems.